2022
DOI: 10.2106/jbjs.22.00389
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transverse Versus Longitudinal Incisions on Anterior Knee Pain After Tibial Nailing (TRAVEL)

Abstract: Background:Anterior knee pain is common after tibial nailing, and its origin is poorly understood. Literature suggests it may be related to infrapatellar nerve injury. The aim of this study was to compare the effect of a transverse (potentially infrapatellar nerve-sparing) incision versus a longitudinal incision for the insertion of a tibial nail with respect to anterior knee pain.Methods:Patients with a tibial shaft fracture undergoing treatment with use of an intramedullary nail were randomized to a transver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
(43 reference statements)
0
2
0
5
Order By: Relevance
“…A substantial number of fractures (30%) did not have a specified nailing approach. One study [ 35 ] reported economic outcomes (Medical Consumption Questionnaire [ 36 ], Productivity Cost Questionnaire [ 37 ], and direct and indirect medical costs).…”
Section: Resultsmentioning
confidence: 99%
“…A substantial number of fractures (30%) did not have a specified nailing approach. One study [ 35 ] reported economic outcomes (Medical Consumption Questionnaire [ 36 ], Productivity Cost Questionnaire [ 37 ], and direct and indirect medical costs).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have advocated for the use of a transverse, rather than longitudinal, incision when utilizing the suprapatellar approach, suggesting that the transverse incision can reduce the risk of infrapatellar nerve injury, potentially reducing rates of anterior knee pain. An RCT of 136 patients demonstrated that the transverse incision resulted in less infrapatellar nerve injury, but anterior knee pain and functional outcomes did not differ 16 .…”
Section: Tibiamentioning
confidence: 99%
“…Essas fraturas podem acometer indivíduos de todas as idades, desde crianças até idosos, com incidência ligeiramente maior no sexo masculino em relação ao sexo feminino. A prevalência de fraturas diafisárias da tíbia pode variar entre diferentes populações devido a variações no estilo de vida, atividades e condições médicas subjacentes 2,3 .…”
Section: Introductionunclassified
“…Lesões relacionadas a esportes, especialmente aquelas que envolvem esportes de contato ou atividades de alto impacto, são outra causa comum de fraturas diafisárias da tíbia. Em alguns casos, essas fraturas também podem ocorrer devido a traumas de baixa energia em indivíduos com ossos enfraquecidos, como aqueles com osteoporose ou tumores ósseos [1][2][3] .…”
Section: Introductionunclassified
See 1 more Smart Citation